Recent Advances in Photocatalytic Transformation of Carbohydrates Into Valuable Platform Chemicals - Chen, Huan; Wan, Kun; Zheng, Fangjuan; Zhang, Zhuo; Zhang, Hongyu; Zhang, Yayun; Long, Donghui (Frontiers in Chemical Engineering, 2021)
In response to the less accessible fossil resources and deteriorating environmental problems, catalytic conversion of the abundant and renewable lignocellulosic biomass to replace fossil resources for the production of value-added chemicals and fuels is of great importance. Depolymerization of carbohydrate and its derivatives can obtain a series of C5-C6 monosaccharides (e.g., glucose and xylose) and their derived platform compounds (e.g., HMF and furfural). Selective transformation of lignocellulose using sustainable solar energy via photocatalysis has attract broad interest from a growing scientific community. The unique photogenerated reactive species (e.g., h+, e−, •OH, •O2−, and 1O2), novel reaction pathways as well as the mild reaction conditions make photocatalysis a “dream reaction.” This review is aimed to provide an overview of the up-to-date contributions achieved in the selective photocatalytic transformation of carbohydrate and its derivatives. Photocatalytic methods, properties and merits of different catalytic systems are well summarized. We then put forward future perspective and challenges in this field.